Peran Sekolah dan Masyarakat dalam Pelaksanaan Program Bantuan Operasional Sekolah - Indahri, Yulia (Pusat Analisis Keparlemenan Badan Keahlian Sekretariat Jenderal DPR RI, 2019)
School Operational Grant (BOS) is a program that absorbs large enough funds and received directly by beneficiaries, schools. The BOS program began on July 2005 in order to accelerate 9-year compulsory education, reduce dropout rates, and assist students from poor families to continue schooling. However, there was also an indication that the government wanted to invite stakeholders, namely schools and the committee, to actively involve in the implementation of the program. Although the funds received by students through their school have not reached the ideal, at least the minimum service requirement can be met. This paper uses literature studies and field studies in three provinces in Indonesia, namely Aceh, West Kalimantan, and North Sulawesi for comparison. Literature studies among which are based on the study and research conducted on the BOS Program by third parties such as SMERU and the World Bank. While field studies were conducted in order to understand problems on the implementation of BOS Program especially on stakeholders’ participation. As conclusion, it is seen that the addition of budget allocations should continue to pay more attention to suggestions from provincial/district/city governments, as well as from the community. Community participation, especially when it comes to funding, should not be unsupervised. There must be certainty of transparency and accountability of the use of funds that are constantly being reported to the public and not of a coercive nature.AbtrakBantuan Operasional Sekolah (BOS) merupakan program yang menyerap dana cukup besar dan langsung diterima oleh penerima bantuan, yaitu sekolah. Program BOS mulai dilaksanakan pada Juli 2005 dalam rangka percepatan Wajib Belajar 9 Tahun, menekan angka putus sekolah, dan membantu siswa dari keluarga miskin untuk dapat terus sekolah. Akan tetapi, ada keinginan dari pemerintah agar pemangku kepentingan, yakni sekolah dan komite sekolah, mau terlibat aktif dalam pelaksanaan program. Walaupun dana yang diterima oleh siswa melalui sekolah belum mencapai angka ideal, paling tidak kebutuhan standar pelayanan minimal dapat terpenuhi. Tulisan ini menggunakan studi pustaka dan studi lapangan di tiga provinsi di Indonesia, yaitu Aceh, Kalimantan Barat, dan Sulawesi Utara untuk perbandingan. Studi pustaka di antaranya adalah kajian dan penelitian yang dilakukan mengenai Program BOS oleh lembaga penelitian SMERU dan juga Bank Dunia. Studi di lapangan dilakukan untuk melihat kendala yang ditemui di lapangan dalam pelaksanaan Program BOS terutama dalam kaitannya dengan peran serta pemangku kepentingan. Dapat disimpulkan bahwa penambahan alokasi anggaran perlu terus mendengarkan masukan dari pemerintah provinsi/kabupaten/kota, dan juga dari masyarakat. Partisipasi masyarakat, terutama jika menyangkut pendanaan, tidak berarti tanpa pengawasan. Harus ada kepastian transparansi dan akuntabilitas dari pemanfaatan dana yang tetap dilaporkan ke masyarakat dan tidak bersifat memaksa.